The MAC OS X Panther book - Ihnatko, Andy (Wiley Publishing, 2004)
This book contains *Developed in cooperation with Apple Computer and written by Mac personality Andy Ihnatko, this book provides entertaining, real-world tips and techniques for getting the most out of Mac OS X Panther ; *Illustrated in full color, this amazing book engages readers with funny and interesting stories as well as expert advice ; *Includes a special section that crystallizes the entire book into a series of "Questions Your Aunt Might Ask You," providing readers with answers to frequently asked questions without resorting to a boring FAQ section ; *Also provides simple, entertaining advice and insider techniques for making the most of Unix, AppleScript, networking, security, customization, and much more